Readers are Reading (Academy of Management Review, 1996)
The article reviews several books, including “Global Disasters: An Inquiry into Management Ethics,” by R. E. Allinson, “Under the Influence Drugs and the American Work Force,” edited by Jacques Norman, Charles P. O'Brien, and Richard O. Lempert, and “Partners for the Dance: Forming Strategic Alliances in Health Care,” edited by Arnold D. Kaluzny, Howard S. Zuckerman, and Thomas C. Ricketts III.